Exploring climate‐related gut microbiome variation in bumble bees: An experimental and observational perspective - Fabienne Maihoff; Lukas Bofinger; Kristof Brenzinger; Alexander Keller; Alice Classen (Ecology, 2025)
Rising temperatures negatively affect bumble bee fitness directly through physiological impacts and indirectly by disrupting mutualistic interactions between bees and other organisms, which are crucial in determining species‐specific responses to climate change. Gut microbial symbionts, key regulators of host nutrition and health, may be the Achilles' heel of thermal responses in insects. They not only modulate biotic interactions with plants and pathogens but also exhibit varying thermal sensitivity themselves. Understanding how environmental changes disrupt microbiome communities is a crucial first step to determine potential consequences for host population responses. We analyzed gut bacterial communities of six bumble bee species inhabiting different climatic niches along an elevational gradient in the German Alps using 16S ribosomal DNA amplicon sequencing. We first investigated whether inter‐ and intraspecific differences in gut bacterial communities can be linked to species' elevational niches, which differ in temperature, flower resource composition, and likely pathogen pressure. A reciprocal translocation experiment between distinct climatic regions tested how the gut bacterial communities of Bombus terrestris and Bombus lucorum change short‐term when exposed to new environments. Finally, we exposed these species to heat and cold wave scenarios within climate chambers to disentangle pure temperature‐driven effects on the microbiome from other environmental effects. Interspecific variation in microbiome composition exceeded intraspecific variation. Species exhibit varying levels of gut microbiome stability, where stability is defined as the within‐group variance: lower stability, indicated by greater within‐group variance, is predominantly observed in species inhabiting higher elevations. Transplanted species showed subtle short‐term gut microbiome adjustments, marked by an increase in Lactobacillaceae upon exposure to warmer regions; however, the gut microbiomes of these bumble bees did not change under laboratory temperature scenarios. We conclude that marked differences in the gut microbiomes of bumble bees could lead to species‐specific responses to environmental change. For example, less stable microbiomes in bumble bees inhabiting higher elevations might indicate an increased sensitivity to pathogens. Short‐term microbiome changes following translocation indicate that species with relatively stable microbiomes, such as B. lucorum and B. terrestris , can rapidly integrate new bacteria, which could increase their capacity to cope with new environments under climate change.